2019
DOI: 10.1021/acssuschemeng.8b04343
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization and Glass-Forming Ability of Ionic Liquids: Novel Insights into Their Thermal Behavior

Abstract: This work presents an extended study of the thermal behavior of the alkyl and dialkylpyridinium derivatives of the bis­(trifluoromethylsulfonyl)­imide ionic liquid series, using high resolution power compensation differential scanning calorimetry (DSC) equipment. Temperatures, enthalpies, entropies, and the heat capacity change associated with the glass transition, as well as cold crystallization, solid–solid transitions, and melting, are used to evaluate their ability to form a glass and crystallize. The effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 64 publications
4
15
0
Order By: Relevance
“…The thermal properties of ionic liquids are essential when it comes to their application, e.g., in supercapacitors, solar cells, batteries, impurities extraction, chemical reactions, and catalysis media [ 16 ]. The literature reports data about the thermal behavior of imidazolium and/or pyridinium ILs, usually obtained with the use of various methodologies (with various scanning rates, annealing periods, sample size, thermal history, and sample purity) [ 17 ]. To the best of our knowledge a complete series of alkyltriethylammonium bis(trifluoromethanesulfonyl)imides (C 4 –C 16 alkyl chain length) has never before been examined thoroughly in terms of their molecular dynamics and thermal behavior.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The thermal properties of ionic liquids are essential when it comes to their application, e.g., in supercapacitors, solar cells, batteries, impurities extraction, chemical reactions, and catalysis media [ 16 ]. The literature reports data about the thermal behavior of imidazolium and/or pyridinium ILs, usually obtained with the use of various methodologies (with various scanning rates, annealing periods, sample size, thermal history, and sample purity) [ 17 ]. To the best of our knowledge a complete series of alkyltriethylammonium bis(trifluoromethanesulfonyl)imides (C 4 –C 16 alkyl chain length) has never before been examined thoroughly in terms of their molecular dynamics and thermal behavior.…”
Section: Resultsmentioning
confidence: 99%
“…The literature also describes a “2/3 golden rule”, which means that for all compounds, that ratio of the temperatures of glass transition and melting (T g /T m ) is around 0.66 [ 20 ]. Lately, it was shown that for aprotic ionic liquids, the usual value of the ratio is 0.75 [ 17 ]. In the case of the [TEA-R] series, such values could be determined only for two ILs—[TEAC 10 ][TFSI] and [TEAC 12 ][TFSI]—because they were the only ones for which both melting point and glass transition temperatures were exhibited.…”
Section: Resultsmentioning
confidence: 99%
“…Xu and Angell (2003) have discussed the Tg dependence on the molar volume (Figure 7B). Recently, Ferreira et al (2019) and Serra et al (2017) have shown that many of the aprotic ILs show high Tg/Tm values that are close to the 34 value.…”
Section: Ils As Glass Forming Materialsmentioning
confidence: 92%
“…Some works have tackled the prediction of the Tg of ILs (Mirkhani et al, 2012; Valderrama et al, 2017). Other studies have identified difficulties behind observing IL's crystallization (Serra et al, 2017; Ferreira et al, 2019).…”
Section: Ils As Glass Forming Materialsmentioning
confidence: 99%
“…The melting point initially decreases with the increase of n C until a critical number after which there is a change of tendency and the melting point starts to increase with n C . [7][8][9] The initial decrease is attributed to a dominant effect of the increase of conformational entropy in the liquid phase as the chain gets longer, while the increase for longer chains is explained as a predominance of the enthalpy resulting from van der Waals and hydrophobic interactions between chains. 8,9 The possibility of different conformers results in the existence of different polymorphs in the solid phase that differ from each other mainly due to the conformation of some dihedral angle.…”
Section: Introductionmentioning
confidence: 99%